Redefinisi Makna Partisipasi Publik Dalam Pembentukan Undang-Undang Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Lalu Hartawan Mandala Putra; Durohim Amnan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
When society thinks that there was a mistake by the state when passing a legal product, then this really happens because society is a condition sine qua non (absolute requirement) in making laws. Just as the recent law formation process does not reflect the meaning of meaningful participation. Laws were formed hastily without heeding the voices of the people. The type of research used is library research using a statutory approach to see whether the case is justified by positive law and justified by the norms that exist in society. Meanwhile, the analysis used is juridical-normative analysis. The aim of this research is to show that there are irregularities in law makers, especially in recent years, who have considered public participation as unimportant. The finding in this work is that the lack of public participation has been a problem for a long time. The meaning of participation so far has only been defined as the participation of